1989
DOI: 10.1523/jneurosci.09-12-04430.1989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine depletion on striatal neurotensin: biochemical and immunohistochemical studies

Abstract: Interactions between striatal dopamine (DA) and neurotensin (NT) have been suggested by anatomical, behavioral, and biochemical studies. Nigrostriatal DA neurons, in contrast to mesocotticolimbic DA neurons, do not appear to contain NT. Thus, distinct neuronal elements subserve interactions between DA and NT within the striatum. We have previously demonstrated that reserpine-induced depletion of striatal DA is accompanied by a dose-and time-dependent increase in striatal NT concentrations. In order to further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…This suggestion is consistent with several studies that have reported that D 2 antagonists and other treatments that disrupt dopaminergic function result in the appearance of at least two distinct populations of NT neurons (38)(39)(40)(41)(42). One of these groups of NT cells is concentrated in the matrix compartment of the dorsomedial and ventrolateral striata; these cells rarely express Fos (38,42).…”
Section: Regionally Distinct Changes In Fos Expression In Ntsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggestion is consistent with several studies that have reported that D 2 antagonists and other treatments that disrupt dopaminergic function result in the appearance of at least two distinct populations of NT neurons (38)(39)(40)(41)(42). One of these groups of NT cells is concentrated in the matrix compartment of the dorsomedial and ventrolateral striata; these cells rarely express Fos (38,42).…”
Section: Regionally Distinct Changes In Fos Expression In Ntsupporting
confidence: 92%
“…Whereas the observation that D 2 antagonist administration results in the appearance of NT cells that were previously below detection threshold suggests that basal functional activity of these cells may be low, several in vivo microdialysis studies have found detectable levels of NT in the striatum (39,51,52), consistent with a tonic regulation of striatal function by NT.…”
Section: Mechanisms Through Which Nt Loss Could Attenuate Haloperidolmentioning
confidence: 99%
“…With the hal-SCH combo used in this study, we sought to replicate complete dopamine depletion based on empirical data showing that an extraordinary effect on the distribution of striatal neurotensin immunoreactivity caused by reserpine (Bean et al, 1989) was reproduced only with a combo of hal and SCH at these doses (Zahm, 1992). Lesser doses of dopamine antagonist and dopamine-depleting 6-hydroxydopamine lesions failed to replicate the unique effect of reserpine, so the drug effect was attributed to the production of CNS extracellular concentrations of antagonist adequate to achieve full blockade of dopamine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Wagstaff et al (1996) recently reported in vivo microdialysis data showing that the D 2-like antagonist eticlopride produces decreased extracellular neurotensin in the nucleus accumbens and a medial part of the dorsal striatum, which in the same condition exhibit increases in NT/N mRNA synthesis (present results; see also . Conversely, Wagstaff et al (1996) reported no change in extracellular neurotensin in the lateral part of dorsal striatum (see also Bean et al, 1989), where synthesis under this pharmacologic condition has been shown to be very robust (Merchant et al, 1991;Augood et al, 1991;. Finally, Wagstaff et al (1996) observed that increased extracellular levels of neurotensin were generated in the nucleus accumbens in response to administration of quinpirole, a dopamine D 2-like agonist that has no reported stimulatory effect on accumbal NT/N mRNA or peptide synthesis (Merchant and Dorsa, 1993;Zahm, unpublished observations).…”
Section: Neurotensin Synthesis Vs Release Vs Degradation Quagmire Rmentioning
confidence: 97%
“…As in a number of previous studies from this laboratory (Eggerman and Zahm, 1988;Zahm and Johnson, 1989;Zahm, 1992;Senger et al, 1993;Zahm, 1995, 1996), the analysis of the material in the present study relied on the observation that neurotensin peptide and NT/N mRNA are present in largely undetectable or barely detectable amounts in neurons in much of the dorsal striatum of naive and vehicle-treated rats (see also Jennes et al, 1982;Bean et al, 1989). Thus, increases in the areal density of immunolabeled and hybridized neurons in response to drug treatments were interpreted as increases in the amount of neurotensin or its NT/N mRNA in neurons to levels exceeding a threshold for detection.…”
Section: Detection and Quantitation Of Neurotensin And Nt/n Mrnamentioning
confidence: 99%